A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

Serum per- and polyfluoroalkyl substances (PFAS) concentrations and anti-spike SARS-CoV-2 IgG levels following COVID-19 vaccination: A cross-sectional study in three communities with elevated PFAS exposure - Sarah Rhea; David Collier; Michael Cuffney; C. Suzanne Lea; Nadine Kotlarz; Jane A. Hoppin (International Journal of Hygiene and Environmental Health, 2026)

Longest documented coastal migrations of shortnose sturgeon - Joseph D. Nolan; William C. Post; Ellen Waldrop; Joseph J. Facendola; Michael S. Loeffler; William Collier; Evan C. Ingram; Martin J. Hamel; Adam G. Fox (Journal of Fish Biology, 2025)
The shortnose sturgeon (SNS; Acipenser brevirostrum ) is a United States federally endangered diadromous species. Although SNS spend much of their time in riverine habitat, inter‐river migrations have been documented in northern populations. However, the inter‐river migratory behaviour and distance capabilities of southern SNS are poorly understood. In this communication, we describe two SNS that migrated approximately 425 km across the coast, far exceeding the previously reported maximum coastal migration distance for the species. These observations offer critical updates for species descriptions and management regarding the coastal migration ability of SNS.

Small step in tech needed to upscale tropical island eradications - A. J. Burt; G. Harper; D. Ringler; M. Cagnato; L. A. Turnbull; J. C. Russell; A. Samaniego; T. Collier; S. Steibl; P. Carr; J. C. Daltry; A. Constance; et al. (Biological Invasions, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Amantadine interactions with phase separated lipid membranes - Jacob J. Kinnun; Jan Michael Y. Carrillo; C. Patrick Collier; Micholas Dean Smith; John Katsaras (Chemistry and Physics of Lipids, 2024)

Behavioural responses of Sandwich terns following the construction of offshore wind farms - Chris B. Thaxter; Ros M. W. Green; Mark P. Collier; Rachel C. Taylor; Robert P. Middelveld; Emily S. Scragg; Lucy J. Wright; Aonghais S. C. P. Cook; Ruben C. Fijn (Marine Biology, 2024)

Heritable differences in abundance of bacterial rhizosphere taxa are correlated with fungal necrotrophic pathogen resistance - Cloe S. Pogoda; Kyle G. Keepers; Stephan Reinert; Zahirul I. Talukder; Brian C. Smart; Ziv Attia; Jason A. Corwin; Kennedy L. Money; Erin C. E. Collier‐zans; William Underwood; Thomas J. Gulya; C. Alisha Quandt; et al. (Molecular Ecology, 2024)
Host–microbe interactions are increasingly recognized as important drivers of organismal health, growth, longevity and community‐scale ecological processes. However, less is known about how genetic variation affects hosts' associated microbiomes and downstream phenotypes. We demonstrate that sunflower ( Helianthus annuus ) harbours substantial, heritable variation in microbial communities under field conditions. We show that microbial communities co‐vary with heritable variation in resistance to root infection caused by the necrotrophic pathogen Sclerotinia sclerotiorum and that plants grown in autoclaved soil showed almost complete elimination of pathogen resistance. Association mapping suggests at least 59 genetic locations with effects on both microbial relative abundance and Sclerotinia resistance. Although the genetic architecture appears quantitative, we have elucidated previously unexplained genetic variation for resistance to this pathogen. We identify new targets for plant breeding and demonstrate the potential for heritable microbial associations to play important roles in defence in natural and human‐altered environments.

Factors associated with per- and polyfluoroalkyl substances (PFAS) serum concentrations in residents of New Hanover County, North Carolina: The GenX exposure study - Michael Cuffney; Adrien A. Wilkie; Nadine Kotlarz; Detlef Knappe; C Suzanne Lea; David N. Collier; Jamie DeWitt; Jane A. Hoppin (Environmental Research, 2023)

A new deglacial climate and sea-level record from 20 to 8 ka from IODP381 site M0080, Alkyonides Gulf, eastern Mediterranean - Ilaria Mazzini; Thomas M. Cronin; Robert L. Gawthorpe; Richard E. Ll Collier; Gino de Gelder; Anna Rose Golub; Michael R. Toomey; Robert K. Poirier; Huai-Hsuan May Huang; Marcie Purkey Phillips; Lisa C. McNeill; Donna J. Shillington (Quaternary Science Reviews, 2023)

Application of a 3D hydrogel-based model to replace use of animals for passaging patient-derived xenografts - Sal Jones; Jennifer C. Ashworth; Marian Meakin; Pamela Collier; Catherine Probert; Alison A. Ritchie; Catherine L. R. Merry; Anna M. Grabowska (In vitro models, 2023)
Purpose This 3D in vitro cancer model for propagation of patient-derived cells, using a synthetic self-assembling peptide gel, allows the formation of a fully characterised, tailorable tumour microenvironment. Unlike many existing 3D cancer models, the peptide gel is inert, apart from molecules and motifs deliberately added or produced by cells within the model. Methods Breast cancer patient-derived xenografts (PDXs) were disaggregated and embedded in a peptide hydrogel. Growth was monitored by microscopic examination and at intervals, cells were extracted from the gels and passaged on into fresh gels. Passaged cells were assessed by qPCR and immunostaining techniques for the retention of characteristic markers. Results Breast cancer PDXs were shown to be capable of expansion over four or more passages in the peptide gel. Contaminating mouse cells were found to be rapidly removed by successive passages. The resulting human cells were shown to be compatible with a range of common assays useful for assessing survival, growth and maintenance of heterogeneity. Conclusions Based on these findings, the hydrogel has the potential to provide an effective and practical breast cancer model for the passage of PDXs which will have the added benefits of being relatively cheap, fully-defined and free from the use of animals or animal products. Encapsulated cells will require further validation to confirm the maintenance of cell heterogeneity, genotypes and phenotypes across passage, but with further development, including the addition of bespoke cell and matrix components of the tumour microenvironment, there is clear potential to model other cancer types.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Mapping biological soil crusts in a Hawaiian dryland - Eszter A. Collier; Ryan L. Perroy; Sasha C. Reed; Jon P. Price (International Journal of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genetic loci underlying quantitative resistance to necrotrophic pathogens Sclerotinia and Diaporthe (Phomopsis), and correlated resistance to both pathogens - Cloe S. Pogoda; Stephan Reinert; Zahirul I. Talukder; Ziv Attia; Erin C. E. Collier-zans; Thomas J. Gulya; Nolan C. Kane; Brent S. Hulke (Theoretical and Applied Genetics, 2021)

Impact of free-living pattern of sedentary behaviour on intra-day glucose regulation in type 2 diabetes - Aye C. Paing; Kathryn A. McMillan; Alison F. Kirk; Andrew Collier; Allan Hewitt; Sebastien F. M. Chastin (European Journal of Applied Physiology, 2020)
Purpose To investigate how the pattern of sedentary behaviour affects intra-day glucose regulation in type 2 diabetes. Methods This intensive longitudinal study was conducted in 37 participants with type 2 diabetes (age, 62.8 ± 10.5 years). Glucose and sedentary behaviour/physical activity were assessed with a continuous glucose monitoring (Abbott FreeStyle Libre) and an activity monitor (activPAL3) for 14 days. Multiple regression models with generalised estimating equations (GEEs) approach were used to assess the associations of sedentary time and breaks in sedentary time with pre-breakfast glucose, pre-lunch glucose, pre-dinner glucose, post-breakfast glucose, post-lunch glucose, post-dinner glucose, bedtime glucose, the dawn phenomenon, time in target glucose range (TIR, glucose 3.9–10 mmol/L) and time above target glucose range (TAR, glucose > 10 mmol/L). Results Sedentary time was associated with higher pre-breakfast glucose ( p = 0.001), pre-dinner glucose ( p < 0.001), post-lunch glucose ( p = 0.005), post-dinner glucose ( p = 0.013) and the dawn phenomenon ( p < 0.001). Breaks in sedentary time were associated with lower pre-breakfast glucose ( p = 0.023), pre-dinner glucose ( p = 0.023), post-breakfast glucose ( p < 0.001) and the dawn phenomenon ( p = 0.004). The association between sedentary time and less TIR ( p = 0.022) and the association between breaks in sedentary time and more TIR ( p = 0.001) were also observed. Conclusions Reducing sedentary time and promoting breaks in sedentary time could be clinically relevant to improve intra-day glucose regulation in type 2 diabetes.

Global challenges for seagrass conservation - Richard K. F. Unsworth; Len J. McKenzie; Catherine J. Collier; Leanne C. Cullen-Unsworth; Carlos M. Duarte; Johan S. Eklöf; Jessie C. Jarvis; Benjamin L. Jones; Lina M. Nordlund (Ambio, 2019)

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Neuroprotective activity of leukemia inhibitory factor is relayed through myeloid zinc finger-1 in a rat model of stroke - Stephanie M. Davis; Lisa A. Collier; Elspeth A. Foran; Christopher C. Leonardo; Craig T. Ajmo; Keith R. Pennypacker (Metabolic Brain Disease, 2019)

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

The fate of genes that cross species boundaries after a major hybridization event in a natural mosquito population - Mark J. Hanemaaijer; Travis C. Collier; Allison Chang; Chloe C. Shott; Parker D. Houston; Hanno Schmidt; Bradley J. Main; Anthony J. Cornel; Yoosook Lee; Gregory C. Lanzaro (Molecular Ecology, 2018)
Animal species are able to acquire new genetic material via hybridization and subsequent introgression. However, little is known about how foreign genomic material is incorporated into a population over time and what genes are susceptible to introgression. Here, we follow the closely related mosquito sister species Anopheles coluzzii and Anopheles gambiae in a sympatric natural population in Mali at multiple time points spanning a period of 25 years. During this period, we observed the temporary breakdown of mating barriers, which allowed us to explore the fate of alleles that crossed the species boundary in a natural population. Whole genome sequencing of 74 individuals revealed introgression within only 34 genes (0.26% of total genes) from A. gambiae to A. coluzzii , the majority contained within a 4 Mb region on the 2L chromosome which includes the insecticide resistance gene (AGAP004707). We designed a genotyping assay to follow 25 of the 34 introgressed alleles over time and found that all A. gambiae alleles, except four, reached a frequency of 50% in the A. coluzzii population within 4 years (~50 generations) and increased to ~80% within 6 years (~75 generations). However, the frequency of all introgressed alleles, except three, decreased to ~60% in 2016. This suggests an ongoing process of purifying selection in the population against DNA of foreign ancestry, except for alleles that are under positive selection, resulting in a complex genomic landscape . This study shows that stable introgression is limited to only specific genes even within closely related species.

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Early life traits of farm and wild A tlantic salmon S almo salar and first generation hybrids in the south coast of N ewfoundland - D. Hamoutene; J. Perez‐Casanova; K. Burt; L. Lush; J. Caines; C. Collier; R. Hinks (Journal of Fish Biology, 2017)
This study examined fertilization rates, survival and early life‐trait differences of pure farm, wild and first generation ( F1 ) hybrid origin embryos after crossing farm and wild Atlantic salmon Salmo salar . Results show that despite a trend towards higher in vitro fertilization success for wild females, differences in fertilization success in river water are not significantly different among crosses. In a hatchery environment, wild females' progeny (pure wild and hybrids with wild maternal parent) hatched 7–11 days earlier than pure farm crosses and hybrids with farm maternal parents. In addition, pure wild progeny had higher total lengths ( L T ) at hatch than pure farm crosses and hybrids. Directions in trait differences need to be tested in a river environment, but results clearly show the maternal influence on early stages beyond egg‐size differences. Differences in L T were no longer significant at 70 days post hatch (shortly after the onset of exogenous feeding) showing the need to investigate later developmental stages to better assess somatic growth disparities due to genetic differences. Higher mortality rates of the most likely hybrids (farm female × wild male hybrids) at egg and fry stages and their delayed hatch suggest that these F1 hybrids might be less likely to survive the early larval stages than wild stocks.

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Leukemia Inhibitory Factor Protects Neurons from Ischemic Damage via Upregulation of Superoxide Dismutase 3 - Stephanie M. Davis; Lisa A. Collier; Christopher C. Leonardo; Hilary A. Seifert; Craig T. Ajmo; Keith R. Pennypacker (Molecular Neurobiology, 2017)

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

Belowground interactions between Kalmia angustifolia and Picea mariana: roles of competition, root exudates and ectomycorrhizal association - Azim U. Mallik; Shekhar R. Biswas; Laura C. Siegwart Collier (Plant and Soil, 2016)

Long-term efavirenz use is associated with worse neurocognitive functioning in HIV-infected patients - Qing Ma; Florin Vaida; Jenna Wong; Chelsea A. Sanders; Yu-ting Kao; David Croteau; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; Justin C. McArthur; Susan Morgello; et al. (Journal of NeuroVirology, 2016)

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

Complex genome evolution in Anopheles coluzzii associated with increased insecticide usage in Mali - Bradley J. Main; Yoosook Lee; Travis C. Collier; Laura C. Norris; Katherine Brisco; Abdrahamane Fofana; Anthony J. Cornel; Gregory C. Lanzaro (Molecular Ecology, 2015)
In certain cases, a species may have access to important genetic variation present in a related species via adaptive introgression. These novel alleles may interact with their new genetic background, resulting in unexpected phenotypes. In this study, we describe a selective sweep on standing variation on the X chromosome in the mosquito Anopheles coluzzii , a principal malaria vector in West Africa. This event may have been influenced by the recent adaptive introgression of the insecticide resistance gene known as kdr from the sister species Anopheles gambiae . Individuals carrying both kdr and a nearly fixed X‐linked haplotype, encompassing at least four genes including the P450 gene CYP 9K1 and the cuticular protein CPR 125 , have rapidly increased in relative frequency. In parallel, a reproductively isolated insecticide‐susceptible A. gambiae population (Bamako form) has been driven to local extinction, likely due to strong selection from increased insecticide‐treated bed net usage.

Responses of three tropical seagrass species to CO2 enrichment - Y. X. Ow; C. J. Collier; S. Uthicke (Marine Biology, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Littoral and benthic macroinvertebrate community responses to contrasting stressors in a large New Zealand river - Kevin J Collier; Mark P Hamer; Stephen C Moore (New Zealand Journal of Marine and Freshwater Research, 2014)
Large rivers present major challenges for biomonitoring and the development of biocriteria because of difficulties obtaining samples representative of the range of habitats present and a paucity of information on taxa responses to environmental conditions. We sampled littoral and deepwater benthic habitats to investigate macroinvertebrate community composition associated with organic, sediment and heated water discharges at 22 transects along a 73 km section of the lower Waikato River, North Island, New Zealand. Significant community differences in near‐field exposure versus no exposure sites were found only in littoral habitats, partly reflecting changes in relative abundances of Crustacea and Oligochaeta. Littoral and benthic habitats supported different macroinvertebrate communities, particularly downstream of the sediment input and following the onset of a river‐floodplain morphology which may have enhanced deposition of suspended sediment. Distance down river was a significant covariate for most metrics derived from benthic samples, but did not influence the relative abundance of most macroinvertebrate groups in littoral samples. Collectively, these results suggest that littoral habitats are likely to be more suitable than benthic habitats for biomonitoring since macroinvertebrate faunas were responsive to near‐field stressor exposure and were less likely to be influenced by longitudinal changes in river conditions.

Natural variations in xenobiotic-metabolizing enzymes: developing tools for coral monitoring - L. R. A. Rougée; R. H. Richmond; A. C. Collier (Coral Reefs, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Using genetic findings in autism for the development of new pharmaceutical compounds - Jacob A. S. Vorstman; Will Spooren; Antonio M. Persico; David A. Collier; Stefan Aigner; Ravi Jagasia; Jeffrey C. Glennon; Jan K. Buitelaar (Psychopharmacology, 2014)

Open letter to the European commission: scientifically unfounded precaution drives European commission’s recommendations on EDC regulation, while defying common sense, well-established science, and risk assessment principles - Daniel Dietrich; Sonja von Aulock; H. W. J. Marquardt; Bas J. Blaauboer; Wolfgang Dekant; James Kehrer; Jan G. Hengstler; Abby C. Collier; Gio Batta Gori; Olavi Pelkonen; Florian Lang; Frans P. Nijkamp; et al. (Archives of Toxicology, 2013)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

Environmental variability during the Last Interglacial: a new high‐resolution pollen record from Tenaghi Philippon, Greece - Alice M. Milner; Ulrich C. Müller; Katherine H. Roucoux; Richard E. L. Collier; Jörg Pross; Stavros Kalaitzidis; Kimon Christanis; Polychronis C. Tzedakis (Journal of Quaternary Science, 2013)
A new high‐resolution Last Interglacial pollen record from the Tenaghi Philippon peatland, northeast Greece, documents variability in forest composition and cover, which we attribute to changes in temperature and moisture availability. The declining stage of the interglacial was marked by a stepwise decrease in temperate tree populations and culminated in the complete collapse of forest at the onset of the ensuing stadial. The coincidence of the onset of the stepwise declining trend with the increased prominence of North Atlantic ice‐rafting events suggests that ecological thresholds in southern Europe were only crossed once ice rafting events intensified, and implies that changes in North Atlantic ocean circulation were an important contributing factor to the declining temperate forest cover in southern Europe. Our results provide evidence for intra‐interglacial variability in the low mid latitudes and suggest a coupling between the high northern latitudes and the northeast Mediterranean during this interval. Copyright © 2013 John Wiley & Sons, Ltd.

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

CCL20 Is Associated with Neurodegeneration Following Experimental Traumatic Brain Injury and Promotes Cellular Toxicity In Vitro - Christopher C. Leonardo; James Musso; Mahasweta Das; Derrick D. Rowe; Lisa A. Collier; Shyam Mohapatra; Keith R. Pennypacker (Translational Stroke Research, 2012)

The spleen contributes to stroke induced neurodegeneration through interferon gamma signaling - Hilary A. Seifert; Christopher C. Leonardo; Aaron A. Hall; Derrick D. Rowe; Lisa A. Collier; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Metabolic Brain Disease, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Characterisation of amyloid-induced inflammatory responses in the rat retina - D. R. Howlett; S. T. Bate; S. Collier; A. Lawman; T. Chapman; T. Ashmeade; I. Marshall; P. J. B. Anderson; K. L. Philpott; J. C. Richardson; C. J. Hille (Experimental Brain Research, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Roles of cortisol and carbonic anhydrase in acid–base compensation in rainbow trout, Oncorhynchus mykiss - K. M. Gilmour; C. L. Collier; C. J. Dey; S. F. Perry (Journal of Comparative Physiology B, 2010)

Does post-fire abiotic habitat filtering create divergent plant communities in black spruce forests of eastern Canada? - Laura C. Siegwart Collier; Azim U. Mallik (Oecologia, 2010)

Administration of a Sigma Receptor Agonist Delays MCAO-Induced Neurodegeneration and White Matter Injury - Christopher C. Leonardo; Aaron A. Hall; Lisa A. Collier; Suzanne M. Green; Alison E. Willing; Keith R. Pennypacker (Translational Stroke Research, 2010)

The development of an objective methodology to measure medication adherence to oral thiopurines in paediatric patients with acute lymphoblastic leukaemia—an exploratory study - Ahmed F. Hawwa; Jeff S. Millership; Paul S. Collier; Anthony McCarthy; Sid Dempsey; Carole Cairns; James C. McElnay (European Journal of Clinical Pharmacology, 2009)

Sequence- or Position-Specific Mutations in the Carboxyl-Terminal FL Motif of the Kidney Sodium Bicarbonate Cotransporter (NBC1) Disrupt Its Basolateral Targeting and α-Helical Structure - Hong C. Li; Joel H. Collier; Ali Shawki; Jai S. Rudra; Emily Y. Li; Bryan Mackenzie; Manoocher Soleimani (The Journal of Membrane Biology, 2009)

The Role of Cohort Studies in Drug Development: Clinical Evidence of Antiviral Activity of Serotonin Reuptake Inhibitors and HMG-CoA Reductase Inhibitors in the Central Nervous System - Scott L. Letendre; Jennifer Marquie-Beck; Ronald J. Ellis; Steven Paul Woods; Brookie Best; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina Marra; Justin C. McArthur; J. Allen McCutchan; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2007)

Pleistocene subglacial tunnel valleys in the central North Sea basin: 3‐D morphology and evolution - Lidia Lonergan; Susannah C. R. Maidment; Jenny S. Collier (Journal of Quaternary Science, 2006)
Four phases of cross‐cutting tunnel valleys imaged on 3‐D seismic datasets are mapped within the Middle–Late Pleistocene succession of the central North Sea basin (Witch Ground area). In plan the tunnel valleys form complex anastomosing networks, with tributary valleys joining main valleys at high angles. The valleys have widths ranging from 250 to 2300 m, and base to shoulder relief varying between 30 and 155 m, with irregular long‐axis profiles characteristic of erosion by water driven by glaciostatic pressures. The youngest phase of tunnel valleys are smaller and have a thinner infill than the older generations. The fill of the larger valleys comprises three seismic facies, the lowermost of which has high amplitudes and is discontinuous. The middle facies consists of wedge‐shaped packages of low‐angle dipping reflectors and is overlain by a facies characterised by sub‐horizontal reflectors, which onlap the valley margins. The seismic character, and comparison with lithologies identified in other northwest European Pleistocene tunnel valleys both onshore and offshore, suggests that the lower two seismic facies are most likely sand and gravel‐dominated, while the uppermost facies consists of glaciolacustrine and marine muds. The 3‐D morphology of the valley margins combined with the geometry of the infill packages suggest that episodic discharge of subglacial meltwater was responsible for incising the valleys and depositing at least some of the infill. Proglacial glaciofluvial deposits are inferred to account for some of the fill overlying the subglacial deposits. Glaciolacustrine and marine muds filled remaining valley topography as the ice sheet retreated. The preserved valley margins are shown to be time‐transgressive erosion surfaces that record changes in geometry of the tunnel valley system as it evolved through time, implying that valleys associated with each ice‐sheet advance/retreat cycle were dynamic and probably long‐lived. Within the constraints of the existing stratigraphy the oldest tunnel valleys in the Witch Ground area of the central North Sea are most likely to be Marine Isotope Stage (MIS) 12 (Elsterian, ca. 470 ka) in age and the youngest pre‐MIS 5e (last interglacial, ca. 120 ka). If each tunnel valley phase was formed during the retreat of a major ice sheet then four glaciations with ice coverage of the central North Sea are recorded in the pre‐Weichselian, Middle–Late Pleistocene stratigraphy. Copyright © 2006 John Wiley & Sons, Ltd.

Sex differences in muscle fatigability and activation patterns of the human quadriceps femoris - Brian C. Clark; Scott R. Collier; Todd M. Manini; Lori L. Ploutz-Snyder (European Journal of Applied Physiology, 2005)

Clinical validation of the NeuroScreen - Ronald J Ellis; Scott R Evans; David B Clifford; Lauren R Moo; Justin C McArthur; Ann C Collier; Constance Benson; Ron Bosch; David Simpson; Constantin T Yiannoutsos; Yijun Yang; Kevin Robertson; et al. (Journal of NeuroVirology, 2005)

Phenotypic assessment and mapped markers for H31, a new wheat gene conferring resistance to Hessian fly (Diptera: Cecidomyiidae) - C. E. Williams; C. C. Collier; N. Sardesai; H. W. Ohm; S. E. Cambron (Theoretical and Applied Genetics, 2003)

Ecoregional differences in macrophyte and macroinvertebrate communities between Westland and Waikato: Are all New Zealand lowland streams the same? - I. C. Duggan; K. J. Collier; P. D. Champion; G. F. Croker; R. J. Davies‐Colley; P. W. Lambert; J. W. Nagels; R. J. Wilcock (New Zealand Journal of Marine and Freshwater Research, 2002)
We characterised water chemistry, aquatic habitat, macrophytes, and invertebrate assemblages in eight lowland streams—five in Westland, South Island, and three in the Waikato, North Island, New Zealand. Factors influencing invertebrate community structure over large (between ecoregions) and small (within an ecoregion) spatial scales were investigated. The Westland sites had generally lower nutrient concentrations, conductivity, and water clarity, and coarser substrates than the Waikato sites, reflecting differences in geological history, hydrology, and land‐use intensity. The macrophyte communities in each region were very different in species composition and structure, but seasonal abundance patterns in both regions were fairly typical of New Zealand streams in general. Alien obligate submerged macrophyte species were absent from the Westland lowland stream sites, and may partly reflect the isolated nature of this region where colonisation by asexual macrophytes would be difficult. Waikato stream invertebrate faunas were dominated by molluscs (mainly Potamopyrgus ) and crustaceans (mainly amphipods), whereas Epheme‐roptera, Trichoptera, and Coleoptera taxa dominated the Westland stream faunas. The overall structure of invertebrate assemblages appeared to be influenced by a combination of regional differences in substrate type, nutrient concentrations, water clarity, and macrophyte cover. Westland streams with more upstream pastoral development had higher proportions of molluscs than those with predominantly forested or scrub catchments. Our study suggests that large‐scale ecoregional differences may override smaller‐scale land‐use effects on lowland stream invertebrate communities, and that management strategies should be developed on an ecoregional basis for lowland stream ecosystems.

A Lectin-Like Wheat Gene Responds Systemically to Attempted Feeding by Avirulent First-Instar Hessian Fly Larvae - Christie E. Williams; Chad C. Collier; Jill A. Nemacheck; Chengzhi Liang; Sue E. Cambron (Journal of Chemical Ecology, 2002)

Evaluation of invertebrate biometrics and the influence of subsample size using data from some Westland, New Zealand, lowland streams - Ian C. Duggan; Kevin J. Collier; Paul W. Lambert (New Zealand Journal of Marine and Freshwater Research, 2002)
The accuracy and variability of six invertebrate biometrics (taxa richness, number of Ephemeroptera, Plecoptera, and Trichoptera (EPT) taxa, % EPT abundance, % dominant taxon, the Macroinvertebrate Community Index (MCI), and Quantitative MCI (QMCI)) were examined using data from four Westland, New Zealand, streams. All metrics except QMCI differed significantly among sites. Taxa richness and number of EPT taxa distinguished the most impacted site from the remaining sites. Significant temporal differences among streams occurred for % EPT abundance and MCI, and there were interaction effects for these plus % dominant taxon and QMCI, indicating that any differences among sites varied through time. Within individual streams, MCI and QMCI had low ( Metric values obtained from random 100‐count subsamples with replacement had low variability (

UV radiation and potential biological effects beneath the perennial ice cover of an antarctic lake - R. L. Kepner; R. A. Wharton; R. D. Collier; C. S. Cockell; W. H. Jeffrey (Hydrobiologia, 2000)

Accumulation and metabolism of carbon-14 labeled benzene, naphthalene, and anthracene by young coho salmon (Oncorhynchus kisutch) - William T. Roubal; Tracy K. Collier; Donald C. Malins (Archives of Environmental Contamination and Toxicology, 1977)

Über Haemagglutinine in Pflanzenextracten - V. A. H. Tiggelman-Van Krugten; C. M. Ostendorf-Doyer; W. A. Collier (Antonie van Leeuwenhoek, 1956)

Bacterien-haemagglutination - W. A. Collier; Sue Tsiew Wong; J. C. de Miranda (Antonie van Leeuwenhoek, 1955)

Bacterien-haemagglutination - W. A. Collier; J. C. de Miranda (Antonie van Leeuwenhoek, 1955)